The Effect of Local Field Dispersion on the Spectral Characteristics of Nanosized Particles and their Composites - PEROVA, TATIANA (Intech, 2011)
Infrared (IR) spectroscopy of micro- and nanosized particles and their composites is currently one of the most important enabling technologies in the development of micro- and nanostructures and their application to various areas of science and technology. Decreasing the characteristic size of metallic, dielectric and semiconductor materials results in a dramatic alteration to their optical, electrical and mechanical properties, allowing the fabrication of new materials with unique physical properties (Lamberti, 2008; Cao, 2004). These alterations in the optical properties are related to a quantum confinement effect, as well as to a dielectric, or electrostatic, confinement effect (Cahay et al., 2001; Chemla & Miller, 1986). The effect of quantum confinement is most pronounced in semiconductor materials, where the transition from the bulk state to the microcrystalline state causes a substantial change in the band structure and an enhancement of the non-linear electrooptical properties. Dielectric, or polarisation, confinement has a wider impact, since it influences the frequencies and intensities of absorption bands in the spectra of any condensed matter, including crystalline and amorphous solids, as well as liquids. This is because considerable changes in the polarisation of micro/nanoparticles occur, depending on their form and orientation with respect to the external electromagnetic field and the details of the spatial restriction.
Fourier Transforms Approach to Scientific Principles
PUBLISHED
Rijeka, Croatia
Keywords: Optics; quantum confinement; micro/nanoparticles